Article RETRACTED due to manipulation by the authors Nutritional Strategies for Rapid Recovery in Sport: A Literature Review - fadli Ihsan; Zhanneta Kozina; Sukendro Sukendro; Ahmad Nasrulloh; Rezha Arzhan Hidayat; satya Perdana (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background and Goal of Study: Rapid recovery after training or competition is a crucial factor in improving athlete performance and preventing sports injuries. Nutrition plays an important role in this recovery process. This literature review aimed to investigate nutritional strategies that can accelerate the recovery process in sports.